2022
DOI: 10.1007/s11356-022-20099-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating possibility of achieving sustainable development goals through renewable energy, technological innovation, and entrepreneur: a study of global best practice policies

Abstract: This study is anchored on the global best practice policies for achieving sustainable goals for Malaysia. Malaysia is among the countries that made commitment at 2015 United Nations Climate Change Conference to reduce its carbon emissions by 2030. This is expected to contribute to the country’s sustainable development. Malaysian quarterly data of 1992Q1–2019Q4 with relevant policy-based instruments (renewable energy policy, technological innovations, financial development, and entrepreneur activities) are adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…(Saqib, 2022) use a co-integration test in conjunction with nonlinear Granger causality testing to establish that, there is neither short-nor long-term price relationship between crude oil and food product prices. Philip et al (2022) used a nonlinear autoregressive distributed lag model (NARDL) to examine the Malaysian instance. As a result of this research, no long-term association between the factors studied was discovered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Saqib, 2022) use a co-integration test in conjunction with nonlinear Granger causality testing to establish that, there is neither short-nor long-term price relationship between crude oil and food product prices. Philip et al (2022) used a nonlinear autoregressive distributed lag model (NARDL) to examine the Malaysian instance. As a result of this research, no long-term association between the factors studied was discovered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A similar study was conducted in Pakistan by (M. K. Khan et al, 2019), who found the same results as (Islam et al, 2021) with the exception that energy consumption affects the CO2 emissions positively and innovation affects it inversely. Accordingly, in Malaysia, Philip et al (2022) observed that renewable energy, technological innovations, and entrepreneur activities reduce the CO2 emissions. Furthermore, using both symmetric (DOLS) and asymmetric (NARDL) methods, found the same findings in Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In EU region, countries are reluctant to control the adverse effect of CO2 emissions due to the higher dependent on the income level by emphasizing on economic development, energy use, bilateral trade, however, use of renewable energy is playing role as a safeguard against the brutal effect of increasing the CO2 emissions (Radmehr et al, 2021). Philip et al (2022) documented that renewable energy mitigates the CO2 emissions Malaysia. Furthermore, a negative insignificant relationship is detected between REC and CO2 emissions in all the models, while the same linkage is found between RPR and CO2 emissions in model one and 2.…”
Section: Gmm and Fixed-effect Estimationsmentioning
confidence: 99%
“…Meanwhile, others argue that renewables have little impact on environmental damage (Pata & Ahmed, 2022;Udemba and Tosun, 2022). In this respect, according to IAEA, the introduction of nuclear energy in the existing energy mix of developing countries can result in the reduction of global average temperature by two degrees centigrade (Philip et al, 2022;Udemba and Tosun, 2022); at the same time, this introduction would also result in a 15% reduction in the global Carbon di Oxide emission by 15% by 2050, (D. F. Birol, 2021). Carbon emissions have been taken by a majority of the researcher (Pata & Ahmed, 2022;Philip et al, 2022;Samour et al, 2022;Udemba and Tosun, 2022) as standard or proxy for determining the level of pollution, but this proxy has been criticised in the past in favor of ecological footprint (Pata and Caglar, 2021).…”
Section: Frontiers In Energy Researchmentioning
confidence: 99%
“…In this respect, according to IAEA, the introduction of nuclear energy in the existing energy mix of developing countries can result in the reduction of global average temperature by two degrees centigrade (Philip et al, 2022;Udemba and Tosun, 2022); at the same time, this introduction would also result in a 15% reduction in the global Carbon di Oxide emission by 15% by 2050, (D. F. Birol, 2021). Carbon emissions have been taken by a majority of the researcher (Pata & Ahmed, 2022;Philip et al, 2022;Samour et al, 2022;Udemba and Tosun, 2022) as standard or proxy for determining the level of pollution, but this proxy has been criticised in the past in favor of ecological footprint (Pata and Caglar, 2021). The major issue with using the ecological footprint is its inability to determine the pollution level as it can only be used to determine the adverse human impact on the environment caused by human exploitation of natural resources, but it fails to account for biocapacity.…”
Section: Frontiers In Energy Researchmentioning
confidence: 99%